The Role of Social Media in Xenophobic Attack in South Africa (Journal of the Digital Humanities Association of Southern Africa, 2024)
Xenophobia is a pressing issue in South Africa, with frequent instances of violence against immigrants. With the rise of social media, platforms like Twitter reflect public sentiment on this matter. This study examines tweets from 2017 to 2022 about xenophobia in South Africa, using NLP, sentiment analysis, and machine learning to understand public feelings and predict potential xenophobic incidents. The findings aim to help policymakers devise strategies to enhance social cohesion and promote a more inclusive society.
Keywords: Xenophobia; Xenophobic Attack; Twitter; Machine Learning; Sentiment Analysis